Genetic Diversity Analysis of Olive Germplasm (Olea europaea L.) With Genotyping-by-Sequencing Technology - Zhu, Shenlong; Niu, Erli; Shi, Ainong; Mou, Beiquan (Frontiers in Genetics, 2019)
Olive (Olea europaea L.) is a very important edible oil crop and has been cultivated about 4,000 years in Mediterranean area. Due to its nutritional and economic importance, researches on germplasm characterization received extensive attentions. In this study, using the genotyping-by-sequencing (GBS) technology, we carried out genetic diversity analysis on 57 olive cultivars with different geographical origin. Totally, 73,482 high-quality single nucleotide polymorphisms (SNPs) with minor allele frequency (MAF) > 5%, call rate > 50% and heterozygosity rate < 10% were obtained at the whole genome level. Genetic structure and phylogenetic analysis showed that the 57 olive cultivars could be classified into two groups (Group I and Group II). No clear geographical distributions of cultivars were observed generally between the two groups. The average nucleotide diversities (π) specific for Group I and Group II were 0.317 and 0.305. The fixation index (Fst) between Group I and Group II was 0.033. In the Group II, cultivars could be further divided into two subgroups (Group IIa and Group IIb) which seem to be associated with their fruit sizes. The five Chinese bred cultivars were all clustered in Group II, showing a closer genetic relationship with those from the central Mediterranean region and limited genetic background. It is therefore necessary for Chinese olive breeding programs to incorporate other genetic basis by utilizing germplasm from the other regions particularly from east Mediterranean region as breeding parents. The results showed that GBS is an effective marker choice for cultivar characterization and genetic diversity analysis in olive, and will help us better understand the genetic backgrounds of the crop.